Gomer – antyideał żony czy wzorcowa metafora relacji oblubieńczej na podstawie Hieronimowego Komentarza do Oz 1-3? - Jóźwiak, Magdalena (Vox Patrum, 2016)
In this article we included St. Jerome’s standpoint on Gomer — the prostitute and wife of Hosea. This topic was presented in two stages. First, we analysed an issue of ideal woman according to St. Jerome. Then we presented a picture of Gomer in St. Jerome’s comment on the Book of Hosea 1–3. The main point of this article was an attempt to answer a question how St. Jerome deals with conveying the biblical meaning, according to which the prophet on God’s command marries an adulterous woman. This issue is very interesting, because the author of Vulgate had rather unfavourable attitude towards the institution of marriage and Gomer was not only married, but also a prostitute.